Carbon fluxes and species diversity in grazed and fenced typical steppe grassland of Inner Mongolia, China. (12th October 2017) - Sagar, R; Li, G Y; Singh, J S; Wan, Shiqiang
Abstract: Aim: Grasslands are dominant vegetation of China, support outstanding biodiversity and sequester bulk amount of atmospheric CO2 . These grasslands are highly degraded and fragmented due to remarkable anthropogenic and grazing loads. Chinese Government has made great attempt to restore by grazing exclusion. The relations of carbon fluxes with species composition and diversity in the communities sensitive to grazing by large herbivores are needed to be analysed under the global climate change scenario. The objective of present study was to comprehend the effects of grazing and fencing on the ecosystem structure and function of the typical steppe grassland. Methods: To meet the objectives, overgrazed and fenced (since year 2001) systems were selected in typical steppe grassland at the Duolun Restoration Ecology Research Station, Inner Mogolia, China. Within each system, three dominant communities with three replicates were selected. In each replicate community, three 1 × 1 m plots, were randomly located. Each plot was divided into four 50 × 50 cm quadrats. A total of 216, 50 × 50 cm quadrats were sampled. From each quadrat, number of individuals and above-ground herbaceous biomass for each species, soil respiration (SR), ecosystem respiration (ER), net (NEE) as well as gross (GEE) ecosystem CO2 exchanges were recorded in June 2015. Data were well analysed using statistical software. Canonical correspondence analysis showed differential responses of communities to the structure and function of the typical steppe grassland. Important Findings: Across the communities, fencing reduced the soil temperature by 12% and at the same time increased the soil moisture by 44.30%, thus, increased the species richness by 28%, evenness by 21%, above-ground biomass by 19% and plant carbon by 20%. Interestingly, fencing increased NEE by 128%, GEE by 77%, SR by 65% and ER by 39%. Under fencing, species composition partially governed the CO2 exchange processes. Conclusions: Fencing reduces soil temperature and thereby improves species diversity and more efficient CO2 sequestration and long-term and in-depth study is desirable for a better understanding of the relationship between species diversity and ecosystem carbon uptake.